Rough Hesitant Fuzzy Groups - Xueyou Chen (Journal of New Theory)
In 2010, Torra introduced the notion of a hesitant fuzzy set, which is a generalization of Zadeh's fuzzy set. In the paper, we define two rough operators on hesitant fuzzy group by means of a normal hesitant fuzzy subgroup and investigate some of their properties.